Demographic Determinants of the Changes in the Student Population of the Lubelskie Voivodship - Mieczysław Kowerski (Barometr Regionalny, 2012)
Demographic processes are one of the fundamental factors determining the number of students. This article presents the analysis of the demographic processes’ influence on the current and future number of students in the Lubelskie Voivodship — a region of the NUTS 2 level, located in eastern Poland, bordering on Byelorussia and Ukraine. We used the auto-regression model to produce the forecast which indicates that through the year 2035 we will be experiencing drastic, permanent decline in the numbers of Polish students in the Lubelskie Voivodship, caused by the predicted significant decrease in the number of high school pupils.